School-Linked Services Child Opportunity Zone Family Centers - Walsh, Catherine B.; Rhode Island KIDS COUNT, Providence; Brown Univ., Providence, RI. Education Alliance for Equity in the Nation's Schools ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This report is the first of a series focusing on school-linked services, family support programs, and school-family-community partnerships in Rhode Island. The report provides a rationale for school-linked services as a strategy to improve outcomes for children, describes Rhode Island's Child Opportunity Zone (COZ) Family Center initiative, and suggests program and policy implications. Section 1 of the report describes attributes of effective programs for children and families, provides a rationale for school-linked services to promote school readiness and success and improve outcomes for children, and discusses the current state of knowledge about successful school-linked services from family center efforts in other states. This section also presents the guiding principles for the COZ Family Center Initiative; discusses the program foci, including children's learning environments, physical and mental health, economic opportunity, and family support; and describes the incorporation of the Carnegie Corporation Starting Points. Section 2 of the report contains program profiles for 13 communities, with each profile providing information on the population served, the advisory board members, community and school locations, funding levels and sources, program components, contact information, and the focus of current activities. (Contains 24 references.) (KB)
Availability: Rhode Island KIDS COUNT, 70 Elm Street, Providence, RI 02903; phone: 401-351-9400; fax: 401-351-1758; e-mail: rikids@rikidscount.org; World Wide Web: www.rikidscount.org (free).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RJ96006401.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ancillary School Services; Economic Opportunities; Educational Environment; Elementary Secondary Education; Family Programs; Family School Relationship; Integrated Services; Mental Health; Partnerships in Education; Physical Health; Program Descriptions; Public Policy; School Readiness; Family Support; Family Resource and Support Programs -- Rhode Island; Reports, Descriptive